Investigating the Role of Protein Kinase R in the Host Immune Response to Bacterial Infection - Berbatovci, Fjolla (Université d'Ottawa / University of Ottawa, 2025)
Protein Kinase R (PKR) was originally identified as a host protective kinase in response to viral infections. However, PKR was later discovered to play diverse roles in regulating cell signaling, such as inflammation, cell proliferation, and cell death. Recently, there are emerging reports by our lab and others that PKR is also involved in the immune response to bacterial pathogens, including Mycobacterium tuberculosis. However, there are conflicting reports on the role of PKR in the host immune response to different bacterial infections. In this thesis, I show that Listeria monocytogenes (Lm) infection triggers upregulation of PKR expression and increases its activity, as indicated by increased phosphorylation of PKR. Using genetically manipulated macrophages, I show that PKR overexpressing THP-1 macrophages (THP-PKR) promote increased Lm survival and proliferation, while deletion of PKR (THP-ΔPKR) reduce bacterial survival. Furthermore, I demonstrate that enhanced growth of Lm in THP-PKR cells is mediated through type I IFN signaling, as inhibition of the Interferon α/β receptor (IFNAR) restored the ability of THP-PKR macrophages to control Lm growth. Consistent with this observation, immunological profiling of THP-PKR cells indicates an increase in the production of IFN-β and IL-10, and a reduction in TNF-α production. Interestingly, while Lm infection induces cell death in THP-1 macrophages, there were no PKR-dependant differences in cell death observed. In search for a potential functional mechanism, I showed that the effect of PKR on Lm survival was not mediated through modulations of autophagy signaling or changes in reactive oxygen species (ROS) production. However, PKR-mediated survival of Lm can be perturbed by the addition of interferon gamma (IFN-γ), which reduces Lm survival in THP-PKR macrophages to the level of the control cells. This suggests that the functional mechanism of PKR in the context of Lm infection is at least partially mediated through an IFN-γ dependent pathway. Thus, this project aims to highlight the importance of PKR signaling and regulation for the host defense against pathogens.
Keywords: Listera; PKR; Listeria monocytogenes; Type I interferons; Interferons